×

# You're going to love this

Derive the quadratic formula. In other words, in the equation

$ax^2 + bx + c = 0$

change the subject to $$x$$.

Note by Sharky Kesa
2 years, 11 months ago

Sort by:

Quadratic formula can be derived more easily , we will use tschirnhaus transformation for the quadratic (used for reducing quartics and cubics)

The equation can be written as $x^2+\frac{b}{a}x+\frac{c}{a}=0$Use the transformation $$x=y-\frac{b}{2a}$$$\left(y-\frac{b}{2a}\right)^2+\frac{b}{a}\left(y-\frac{b}{2a}\right)+\frac{c}{a}=0$$y^2-\frac{b}{a}y+\frac{b^2}{4a^2}+\frac{b}{a}y-\frac{b^2}{2a^2}+\frac{c}{a}=0$$y^2=\frac{b^2-4ac}{4a^2}$$x+\frac{b}{2a}=\frac{\pm\sqrt{b^2-4ac}}{2a}$$x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$ · 2 years, 11 months ago

This uses the interesting property (for those not too familiar with it)

$\displaystyle \begin{cases}x=y-\frac{a_{n-1}}{n\cdot a_n} \\\\ f(x)=a_n x^n+a_{n-1}x^{n-1}+\cdots+a_1 x+a_0,\: a_n\neq 0\end{cases}$

$\displaystyle \implies f(x)=a_n y^n+p_{n-2}y^{n-2}+p_{n-3}y^{n-3}+\cdots +p_1 y+p_0$ · 2 years, 11 months ago

Rewrite: $x^2+2x \cdot\dfrac{b}{2a}=-\dfrac{c}{a}.$ Add $$(b/2a)^2$$ to both sides and complete square: $x^2+2x \cdot\dfrac{b}{2a}+\left(\dfrac{b}{2a}\right)^2=\left(\dfrac{b}{2a}\right)^2-\dfrac{c}{a} ~\implies \left(x+\dfrac{b}{2a}\right)^2=\dfrac{b^2}{4a^2}-\dfrac{c}{a}=\dfrac{b^2-4ac}{4a^2}.$ Take square root and rearrange: $x+\dfrac{b}{2a}=\dfrac{\pm\sqrt{b^2-4ac}}{2a}~\implies x=\dfrac{-b\pm\sqrt{b^2+4ac}}{2a}.$ · 2 years, 11 months ago

congratulation for 135 / 135 · 2 years, 11 months ago